2021
DOI: 10.1002/cjce.24132
|View full text |Cite
|
Sign up to set email alerts
|

Eichhornia crassipes as biosorbent for industrial wastewater treatment: Equilibrium and kinetic studies

Abstract: Adsorption is an economical and widely used technique for removing dye from wastewater, especially for non-biodegradable pollutants. In this study, the effectiveness of water hyacinth (WH) as an adsorbent for the removal of methylene blue (MB) was conducted in a batch process. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) were used to characterize WH. The influence of operational parameters such as dye concentration, pH, WH dose, and contact time was studied to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…In another report [Othman et al, 2018] where Fe 3 O 4 nanoparticles are also used for MB adsorption, it was shown that by increasing the adsorbent concentration, a removal of 99.6% is achieved and when hydroxyapatite with chitosan/montmorillonite is used [Jaudi et al, 2020] there is a 99.9% removal for MO and 80% for MB. Likewise, for the removal of MB using the E. crassipes treated with water [Prasad et al, 2021;Wanyonyi et al, 2013] there is a percentage of elimination between 79 and 99%, mentioning that this removal is favored with the amount of mass of the adsorbent in solution. There are studies that report the adsorbers that have been pretreated to improve the adsorption capacity, as well as the removal of MB and MO, including Swietenia mahagoni [40] that was treated with NaOH, noting that the percentage of MO removal increases from 34…”
Section: Thermodynamic Analysis Of the Of Mb And Mo Adsorption Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In another report [Othman et al, 2018] where Fe 3 O 4 nanoparticles are also used for MB adsorption, it was shown that by increasing the adsorbent concentration, a removal of 99.6% is achieved and when hydroxyapatite with chitosan/montmorillonite is used [Jaudi et al, 2020] there is a 99.9% removal for MO and 80% for MB. Likewise, for the removal of MB using the E. crassipes treated with water [Prasad et al, 2021;Wanyonyi et al, 2013] there is a percentage of elimination between 79 and 99%, mentioning that this removal is favored with the amount of mass of the adsorbent in solution. There are studies that report the adsorbers that have been pretreated to improve the adsorption capacity, as well as the removal of MB and MO, including Swietenia mahagoni [40] that was treated with NaOH, noting that the percentage of MO removal increases from 34…”
Section: Thermodynamic Analysis Of the Of Mb And Mo Adsorption Processmentioning
confidence: 99%
“…Likewise, for the removal of MB using the E. crassipes treated with water [Prasad et al, 2021;Wanyonyi et al, 2013] there is a percentage of elimination between 79 and 99%, mentioning that this removal is favored with the amount of mass of the adsorbent in solution. There are studies that report the adsorbers that have been pretreated to improve the adsorption capacity, as well as the removal of MB and MO, including Swietenia mahagoni [40] that was treated with NaOH, noting that the percentage of MO removal increases from 34…”
Section: Thermodynamic Analysis Of the Of Mb And Mo Adsorption Processmentioning
confidence: 99%
“…Figure 1e,f, referring to part of the water hyacinth leaf, shows nonhomogeneous structures with some cavities, thus justifying the need to carry out studies with separate parts, since morphology and porosity can influence the adsorption capacity. The presence of an irregular surface, pores, and surface fractures of both the water hyacinth leaf and stem indicate the presence of micropores and a high surface area [46], which are fundamental and important characteristics of adsorbents [47]. Since these small spaces favor the entry of liquids and adsorption [48].…”
Section: Characterization Of Water Hyacinth Biomassmentioning
confidence: 99%
“…The amount adsorbed increased rapidly over time, until the system reached equilibrium in approximately 60 min, after which there was no significant change in concentration, both for stem and leaf, indicating a rapid interaction, which is an extremely favorable parameter (Figure 4). Other lignocellulosic materials report that the adsorption of MB by the water hyacinth plant is significantly improved in solutions where the pH is greater than 2 [46]. The high pH may increase the number of negatively charged binding sites, facilitating the removal of MB by dry biomass surfaces [61].…”
Section: Adsorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation